Design evaluation of automatic bearing offset adjustment for marine propeller shaft - Riyadh Mohammed Bsiso; Zaidi Mohd Ripin; Chan Ping Yi; Muhammad Ikhwan Zaini (Scientific Reports)
Abstract Conventional marine propeller shaft alignment is performed under predetermined conditions of dry-docking or afloat with fully submerged propellers. It may overlook high-risk scenarios of partial propeller immersion or transient conditions during sailing and maneuvering. Factors such as hull deformation, propeller cavitation, imbalanced hydrodynamic forces in shallow waters, and draft changes from cargo shifts or ballast adjustments can cause excessive shaft displacement and large bending moment, negatively affecting the stern tube bearing. Adjusting the bearing offset, while maintaining the bearing clearance, is known to change the bearing reaction force and this effect is used in the automatic control of bearing vertical elevation using the shaft displacement and slope data together at the stern tube, and the reaction force of the intermediate bearing which acts as the control bearing. The shaft data at the stern tube bearing are the observed parameters set not to exceed the limit prescribed by the Classification Societies. This can be achieved by the active elevation adjustment of the intermediate bearing using a hydraulic actuator. To demonstrate the feasibility of this automatic control design, a model of a marine shaft system of a 50,000 DWT medium-range tanker is equipped with an automatic bearing elevation adjustment system with a PID controller. The results showed significant improvement in the shaft bending parameters, where the optimum elevation of the intermediate bearing is calculated at − 0.076 mm instead of − 0.9 mm for static evaluation, resulting in the slope of the shaft at the stern tube bearing of − 0.3 mrad compared to − 0.499 mrad under the operational load conditions. In the specific case of partial propeller immersion, which is often considered the most harmful, the maximum shaft slope at the stern tube bearing improved from 0.427 mrad (static-based setting) to 0.294 mrad using the automatic system, which is below the limit of 0.300 mrad set forth by the classification societies.